Survey Status Gizi Siswa-Siswi SD Negeri 1 Tataaran II Kecamatan Tondano Selatan Tahun 2025 Kabupaten Minahasa - Duta Syahputra Mokoginta; Tony Pandeleke,; Cindy Rantung (STIKES Columbia Asia Medan, 2025)
Nutritional status is the body's condition as a result of the utilization, absorption, and use of food. One of the health and social problems Indonesia is facing is the low nutritional status of its people. Nutrition deficiencies in young students will hinder mental development and brain intelligence in the future. The purpose of this study was to obtain an overview of the nutritional status of students at SD Negeri 1 Tataaran II, South Tondano District, Minahasa Regency.This research uses a descriptive survey. The population of this research are fourth and fifth grade students at Sekolah Dasar Negeri 1 Tataaran II, South Tondano District, totaling 40 students. The sampling technique used was a total population sampling, thus the sample population was 40 students. The instruments used in this study were a weighing scale, anthropometry equipment, and a list of the students’ names. Based on the research results, it was found that the nutritional status based on weight-for-age tended to be good, with 27 students (67.5%) falling into this category. The nutritional status based on height-for-age tended to be normal, with 27 students (67.5%) also in this category, and the nutritional status based on weight-for- height tended to be good, with 27 students (67.5%). In conclusion, the nutritional status of students at SD Negeri 1 Tataaran II, South Tondano District, tends to be sufficient and they generally have a good nutritional status. It is recommended that, to improve nutritional status at the household level, families should consume a diverse and balanced nutritious diet. The school, in collaboration with the health department or community health center, should routinely monitor the nutritional status of students Nutritional status is the body's condition as a result of the utilization, absorption, and use of food. One of the health and social problems Indonesia is facing is the low nutritional status of its people. Nutrition deficiencies in young students will hinder mental development and brain intelligence in the future. The purpose of this study was to obtain an overview of the nutritional status of students at SD Negeri 1 Tataaran II, South Tondano District, Minahasa Regency.This research uses a descriptive survey. The population of this research are fourth and fifth grade students at Sekolah Dasar Negeri 1 Tataaran II, South Tondano District, totaling 40 students. The sampling technique used was a total population sampling, thus the sample population was 40 students. The instruments used in this study were a weighing scale, anthropometry equipment, and a list of the students’ names. Based on the research results, it was found that the nutritional status based on weight-for-age tended to be good, with 27 students (67.5%) falling into this category. The nutritional status based on height-for-age tended to be normal, with 27 students (67.5%) also in this category, and the nutritional status based on weight-for- height tended to be good, with 27 students (67.5%). In conclusion, the nutritional status of students at SD Negeri 1 Tataaran II, South Tondano District, tends to be sufficient and they generally have a good nutritional status. It is recommended that, to improve nutritional status at the household level, families should consume a diverse and balanced nutritious diet. The school, in collaboration with the health department or community health center, should routinely monitor the nutritional status of students